A aprendizagem de matemática em atividades de modelagem - Horn, Carlinho Augustinho (2018)
This work aims to analyze the use of mathematical modeling as a strategy for mathematics teaching in Basic Education schools. Faced with some expectations, we seek to make a study from a theoretical and practical perspective, in order to answer the central question to achieve this research: How does the learning of mathematical concepts in modeling activities associated with other teaching activities occur? It proposes a problem situation that makes use of mathematical modeling, defining a didactic sequence that is associated with other didactic sequences that use different teaching methodologies. The project was developed in the 8th year of elementary education, at the Catharina Seger School of Basic Education, municipality of Palma Sola, SC, a class of thirteen students. Six students formed a group to solve the modeling problem in an extraclass period. The remaining sequences were worked during class math classes in parallel to the development of the modeling activity. The research proposed for the students is the determination of the maximum quantity of fish to be produced in a pond, having as mathematical focus, the calculation of the volume of water of this dam. Two other sequences were elaborated and applied in the class, having complementarity characteristics of the modeling study, aiming at the systematization of mathematical knowledge. It was observed that modeling is a strong promoter of the interest and significance of mathematics, but its applicability restricts the content addressed to those used in modeling and does not provide a discussion of the truth of propositions. Due to these limitations, the use of modeling associated with other teaching techniques is shown as a methodological strategy that combines contextualization, school curricular requirements and deductive aspects of mathematics.